ANALISIS KESELARASAN TUJUAN PEMBANGUNAN BERKELANJUTAN/SUSTAINABLE DEVELOPMENT GOALS (TPB/SDGs) DENGAN RENCANA PEMBANGUNAN JANGKA MENENGAH KABUPATEN ROKAN HULU TAHUN 2016-2021 - Akbar Alfa (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2019)
This SDGs Data Mapping exercise helps us to estimate readiness of Rokan Hulu in applying proposed SDGs indicators to measure SDGs targets; for which indicator data improvement is required and where the data gaps exist. SDGs consist of 17 goals, 169 targets and 241 Indicators (222 Indicator for District). In order to be able to measure the achievements of the SDGs targets, set of indicators are required and data needs to be available to apply those indicators. The exercise was conducted through desk review method by mapping for each SDGs Target existing relevant indicators used or proposed in the local documents: Rokan Hulu Medium- Term Development Plan 2016 - 2021(RPJMD) and others relevant documents as required. The indicators mapping then followed by data mapping for each indicator based on the availabity and quality of data from Statistics Agency (BPS) and line Agencies. The indicators mapping showed 8,11% Similiar and 10,36% Proxy.